2015
DOI: 10.1097/imi.0000000000000130
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of the eSVS Mesh: Modification of Recommended Technique

Abstract: The eSVS Mesh is a knitted wire lattice manufactured in cylindrical sheaths of various diameters, designed to be placed around the outer surface of a saphenous vein graft before use in coronary surgery. The goal is to improve long-term vein graft patency by preventing expansive endothelial injury obviating neointimal hyperplasia and subsequent graft atherosclerosis. Since the First-In-Man feasibility trial of the eSVS Mesh, postmarket studies in Europe and a feasibility trial in the United States are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The presented technique changes several crucial technical issues: the mesh on the SV is placed 3 to 5 mm from the heel of both the anastomoses and care must be exercised in this matter. 8 If the placement is incorrect, the distance between the end of the graft and the beginning of the mesh may be longer than what is optimal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presented technique changes several crucial technical issues: the mesh on the SV is placed 3 to 5 mm from the heel of both the anastomoses and care must be exercised in this matter. 8 If the placement is incorrect, the distance between the end of the graft and the beginning of the mesh may be longer than what is optimal.…”
Section: Discussionmentioning
confidence: 99%
“…7 While long-term results are mandatory, the purpose of this contribution is to report the first clinical use of a new method of mesh implantation which creates more favorable anastomotic geometry, assesses anastomotic geometry, and assures that no kinking or migrating occurs in the early postoperative period. 8 As the vein/mesh is no longer incorporated within the anastomotic suture line, the necessity of creating a mesh/ tissue interface in suturing is no longer required. This technique also allows the avoidance of fibrin sealant and has been accepted as the recommended technique for use of the mesh.…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that trials had confusing confounding variables other than the evaluation of the mesh that could impact results. In fact, the failures were attributed to inappropriate surgical manipulations and modifications of the application technique were suggested [50]. Cell-containing MDs have also been developed.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…This indicated to the authors that these meshes should not be applied at the anastomosis, and may be the result of encompassing this region asymmetrically . Similarly, it was advised after poor patency results in clinical trials that the constrictive Nitinol eSVS mesh not be applied to the anastomoses as it could restrict the blood flow through the graft . A different Nitinol design, VasQ, was devised by Laminate Medical to more easily fit around the venous anastomosis of hemodialysis fistula patients.…”
Section: Design Considerations For External Stentingmentioning
confidence: 99%